Geographical and Level of Local Government Variation on the Phenomenon of Ecological Footprint in Indonesia: Descriptive Analysis - Muhammad Abduh; Dedik Budianta; Arinafril Arinafril; Lili Erina (Sriwijaya Journal of Environment, 2019)
To simplify the description of the damage phenomenon to the earth, the concept of ecological footprint can be used. This concept is not specifically built to calculate the destruction of the earth. This concept calculates how much space (land and water) humans need to produce the resources they need including absorbing the waste they produce. This study calculates Indonesia's ecological footprint by observing variations according to geography and the level of regional government. This research uses the Environmental Care Behavior Survey Year 2013, Village Potential Census Year 2011 and the 2013 National Social Welfare Survey, or SUSENAS. All were surveyed by the Indonesian Central Bureau of Statistics. As a result, Indonesia's ecological footprint is 1.51 gha. At the provincial level, the ecological footprint of Jakarta is the highest compared to other provinces’ of 1.84 gha. While East Nusa Tenggara has the lowest ecological footprint, which is 1.30 gha. Indonesia's ecological footprint follows the general pattern in the world, of higher ecological footprint in urban area compared to other types of regions such as villages, watersheds, beaches, mountains, forests or hilly areas.